Digital media literacy and mathematical performance among the first year college students - Shara Gean G. Dumaboc; Josiel A. Ganiohan; Evan P. Taja-on (Universitas Sarjanawiyata Tamansiswa, 2025)
Digital media literacy is essential in navigating and effectively utilizing digital tools for educational success in today’s technology-driven world. In mathematics education, leveraging these skills enables students to engage with digital resources that support learning and enhance performance, though many still face challenges in integrating these competencies effectively. The study employed a descriptive correlational design to examine digital media literacy and mathematical performance among students. Respondents were selected from seven departments of San Isidro College using stratified random sampling. The study reveals that students exhibit high digital media literacy, reflecting their readiness to utilize digital tools across academic contexts. However, the observed association between digital media literacy and mathematical performance is minimal and statistically insignificant, indicating that digital competencies alone may not substantially influence mathematics outcomes. These findings suggest that while digital media literacy is important, its role in mathematics education requires further contextual alignment to optimize its impact. Moreover, the results highlight the need for more targeted integration of digital tools within mathematics instruction to enhance their educational outcomes.